Kesulitan Belajar Peserta Didik dalam Materi Konsep Dasar Ilmu Geografi di SMA - Ida Kurniawati; Budi Handoyo; Hadi Soekamto; Tuti Mutia (JAMBURA GEO EDUCATION JOURNAL, 2023)
The basic concept material of geography is the first material that must be mastered by high school (SMA) students, but in reality in schools, especially students of SMAN 1 Wongsorejo, students still have difficulty understanding the basic concepts of geography. This research is to describe the difficulties and factors that cause students to have difficulty understanding the material. The research was qualitative in nature with data analysis using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The research subjects consisted of 10 students of class X MIPA/IPS and two geography teachers. Data collection techniques in this study were through observation, interviews, documentation, and recap of students' daily test results. The results showed that SMAN 1 Wongsorejo students experienced difficulties in sub-material concepts, principles, geographic approaches, which were most dominant in principles and geographic approaches. The factors that cause learning difficulties are external factors and internal factors. External factors in the form of learning methods that are less attractive, the teacher does not reflect on learning, the abstract character of basic geography material, high demands for an independent curriculum, teaching materials and media used are less contextual and do not make use of geospatial information. While the internal factors are independence, cooperation, attention, and poor study habits. In improving the quality of learning on these materials, teachers need to conduct classroom action research, carry out peer tutoring, collaborate with colleagues, guidance and counseling teachers, and parents, carry out learning innovations and improve their professionalism